Multi-dimensional investigation and distribution characteristics analysis of gut microbiota of different marine fish in Fujian Province of China - Sun, Hang; Chen, Fangyi; Hao, Hua; Wang, Ke-Jian (Frontiers in Microbiology, 2022)
The gut microbiota plays an important role in animal health and behavior. In marine fish, the composition of the gut microbiota is affected by many complex factors, such as diet, species, and regional factors. Since more than one hundred fish species have been cultured in fish farms along with the 3,324 km coastline of Fujian Province in South China, we chose this region to study the gut microbiota composition of marine commercial fishes because sufficient different species, diets, and regional factors were observed. We investigated the distribution characteristics of the gut microbiota of seven cultured species (Epinephelus akaara, Epinephelus coioides, Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀, Siganus fuscescens, Pagrus major, Lateolabrax japonicus, and Acanthopagrus schlegelii) living in the same aquatic region and one species (E. akaara) living separately in five regions separated by latitude. The impacts of diet, region, and species factors on fish gut microbiota were also evaluated. Diversity and multivariate analyses showed that the patterns of the microbiota were significantly different in different fish species within the same habitat and E. akaara with five latitude regions. Mantel analysis showed that AN, SiO32–, DO, and NO2– were the principal factors affecting the microbial community of E. akaara in the five habitats. Additionally, similar distribution characteristics occurred in different gut parts of different fishes, with an increasing trend of Proteobacteria and Vibrionaceae abundance and a decreasing trend of Firmicutes and Bacillaceae abundance from the foregut to the hindgut. Vibrionaceae was the most abundant family in the content. This study highlights that a persistent core microbiota was established in marine commercial fishes spanning multiple scales. The factors with the greatest effect on fish gut microbiota may be (i) host genetics and (ii) geographic factors rather than the microbiota in the diet and water environment. These core microbes regularly colonized from the foregut to the hindgut, which was driven by their underlying functions, and they were well adapted to the gut environment. Moreover, the microbiota in the content may have contributed more to the gut microbial communities than previously reported. This study could complement basic data on the composition of marine commercial fishes and facilitate relatively complete investigations, which would be beneficial for the healthy and sustainable development of aquaculture.